Effect of Cobb angle and BMI on scoliosis surgery recovery in adolescent idiopathic scoliosis patients - Alsiddiky, Abdulmonem; Alrashoudi, Abdullatef; Sayed, Ahmed AL; Aljerian, Albaraa; Aljomiah, Abeer (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: To assess the effect of Cobb angle and body mass index (BMI) on surgery recovery outcomes in Adolescent Idiopathic Scoliosis (AIS) patients. Materials and Methods: A retrospective study of 79 Adolescent Idiopathic Scoliosis patients who underwent corrective operations, at King Khaled University Hospital, Riyadh, Saudi Arabia was carried out in 2014. The patients were divided according into Cobb’s angle (mild, moderate and severe) and as per weight (healthy weight and overweight). Data of preoperative, intra-operative and postoperative information as well as measures of daily-living activities were collected. Results: The mean age of 79 patients (70females) was 16.6 years. Cobb angle assessment was mild in 41 (51.9%), moderate in 24(30.4%) and 14(17.7%) were severe. Mean surgery and recovery time of patients is statistically significantly different in relation to severity of Cobb’s angle (mild, moderate and severe). There is highly statistically significant difference in mean ranks of days taken for different measures of daily living in relation to severity of Cobb’s angle. The mean values of body mass index have significantly reduced after surgery, when compared with mean values at before surgery. The mean surgery time was statistically significantly higher in over weight patients (5.33 hours). Conclusions: The results show an effect of severity of Cobb angle on recovery measures of patients with AIS, but no effect of BMI. BMI was corrected in these patients after surgery. Prospective studies are required to assess clinical outcomes of post-operative surgery, satisfaction of patients towards their body image and quality of life. Asian Journal of Medical Sciences Vol.7(2) 2015 28-33